2007
DOI: 10.1021/jp067407w
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Oxidative Polymerization of Safranines

Abstract: Phenosafranine and safranine have been oxidized with ammonium peroxydisulfate in acidic aqueous solution. The oxidative coupling of both safranines was proved by gel permeation chromatography demonstrating the presence of oligomeric chains of mass-average molar masses 6500 and 4500 g mol-1 for polyphenosafranine and polysafranine, respectively. A theoretical study of the mechanism of safranine and phenosafranine polymerization was based on the MNDO-PM3 semiempirical quantum chemical computations of the heat of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 57 publications
1
87
2
Order By: Relevance
“…The spectrum of sample prepared with a higher concentration of ammonium hydroxide, Am 1-B, exhibits peaks at similar positions as Am 0.2-B, except for the 1547 cm -1 peak which is absent (Table 4). The peak at 1547 cm -1 can be attributed to the aromatic ring-stretching vibration in a substituted phenazine unit [50,56]. The characteristic band of the PANI emeraldine base at 1379 cm -1 is not present in the spectra of Am 0.2-B and Am 1-B.…”
Section: Oligomeric Microspherical Samples Am 02-b and Am 1-bmentioning
confidence: 97%
See 1 more Smart Citation
“…The spectrum of sample prepared with a higher concentration of ammonium hydroxide, Am 1-B, exhibits peaks at similar positions as Am 0.2-B, except for the 1547 cm -1 peak which is absent (Table 4). The peak at 1547 cm -1 can be attributed to the aromatic ring-stretching vibration in a substituted phenazine unit [50,56]. The characteristic band of the PANI emeraldine base at 1379 cm -1 is not present in the spectra of Am 0.2-B and Am 1-B.…”
Section: Oligomeric Microspherical Samples Am 02-b and Am 1-bmentioning
confidence: 97%
“…The opinions of the participants on this band are not unanimous. A medium peak at 1365 cm −1 corresponds to stretching vibrations in phenazine-type rings or to C-N stretching vibrations [50,55,56]. A shoulder at 1337 cm -1 is attributed to C-N bonding [33], with the C atom belonging to the aromatic ring which is not simply para-substituted but probably 1,2,4-trisubstituted.…”
Section: Granular Pani Samples H and H-bmentioning
confidence: 99%
“…9, the main characteristic bands of polyaniline at 827 cm À1 , 1141 cm À1 , 1301 cm À1 , 1502 cm À1 , 1577 cm À1 could be seen in the FT-IR spectrum, corresponding to CAH vibration out of benzene plane, CAN stretching of ANHA(C 6 H 4 )ANHA, stretching vibration of CAN bond linked with benzenoid ring, benzenoid structure (C@C) and quinoid (C@C, C@N), respectively [45]. However, two new characteristic bands of solid intermediate products appeared at 1416 cm À1 and 1445 cm À1 , attributing to the ring stretching vibrations in a newly formed phenazine segment [46,47]. Therefore, a reasonable mechanism to form the solid intermediate products was speculate (Fig.…”
Section: A Proposed Degradation Path Of Anilinementioning
confidence: 98%
“…420 nm) is the first main step and afterwards, propagation occurs by addition of monomer in the PBQ chains. However, many doubts remain, and more recently it has been suggested that the formation of phenazine-like rings also occurs in aniline polymerization [35,36], while for polypyrrole and poly(thiophene) the formation of radical species is the main step in the polymerization mechanism.…”
Section: Vibronic Techniques (Uv-vis-nir Ftir Raman Resonance Raman)mentioning
confidence: 99%